Improved and sustained triage skills in firemen after a short training intervention. Issue 1 (December 2015) - Nilsson, Abraham; Åslund, Kristian; Lampi, Maria; Nilsson, Helene; Jonson, Carl-Oscar
Abstract Background A previous study has shown no measurable improvement in triage accuracy among physicians attending the Advanced Trauma Life Support (ATLS) course and suggests a curriculum revision regarding triage. Other studies have indicated that cooperative learning helps students acquire knowledge. Objective The present study was designed to evaluate the effectiveness of trauma cards in triage training for firemen. Methods Eighty-six firemen were randomly assigned into two groups: the trauma card group and the direct instruction group. Both groups received the same 30-min PowerPoint lecture on how to perform triage according to the Sort Assess Lifesaving interventions Treatment and transport (SALT) Mass Casualty Triage Algorithm. In the trauma card group, the participants were divided into groups of 3–5 and instructed to triage 10 trauma victims according to the descriptions on the trauma cards. In the direct instruction group, written forms about the same 10 victims were used and discussed as a continuation of the PowerPoint lecture. Total training time was 60 min for both groups. A test was distributed before and after the educational intervention to measure the individual triage skills. The same test was applied again 6 months later. Results There was a significant improvement in triage skills directly after the intervention and this was sustained 6 months later. No significant difference in triage skills was seen between the trauma card group and the direct instruction group. Previous experience of multi-casualty incidents, years in service, level of education or age did not have any measurable effects on triage accuracy. Conclusions One hour of triage training with the SALT Mass Casualty Triage Algorithm was enough to significantly improve triage accuracy in both groups of firemen with sustained skills 6 months later. Further studies on the first assessment on scene versus patient outcome are necessary to provide evidence that this training can improve casualty outcome. The efficacy and validity of trauma cards for disaster management training need to be tested in future studies.